On Weakly Soft Omega Open Functions and Weakly Soft Omega Closed Functions in Soft Topological Spaces - Mahmood, Sabiha I. (Iraqi Journal of Science, 2022)
The main purpose from this paper is to introduce a new kind of soft open sets in softtopological spaces called soft omega open sets and we show that the collection ofevery soft omega open sets in a soft topological space (X,~,E) forms a soft topology  ~on X which is soft finer than  ~. Moreover we use soft omega open sets to defineand study new classes of soft functions called weakly soft omega open functions andweakly soft omega closed functions which are weaker than weakly soft open functionsand weakly soft closed functions respectively. We obtain their basic properties, theircharacterizations, and their relationships with other kinds of soft functions betweensoft topological spaces.